Self-esteem and gender as factor in the type of peer sought for counseling. - Plasencia, Jessica Benid (1994.)
This is a study on the relationship of self-esteem and gender and type of peer sought for counseling among University of the Philippines in the Visayas students. The objective of the study is to find out if there is a relationship between self-esteem and gender, between self-esteem and type of peer sought, and between gender and the type of peer sought. The nature of the students' academic and social relationship problems as well as their reasons for making contacts with upward peer helper and downward peer helper is also studied. The researcher hypothesized that there is no significant relationship between the variables just mentioned. The chi-square test of association is used to test the said hypotheses. The results revealed that there is no significant relationship between self-esteem and gender but there is a significant relationship between self-esteem and type of peer sought, and between gender and type of peer sought
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Peers -- Counseling